The measurement and financial reporting of intellectual capital by portuguese listed companies - Rodrigues, Lúcia Lima (2002)
Conventional financial statements fail to recognise many intangible assets (such as human resources and customer relationships). As a consequence, they are at risk of losing their relevance as a helpful investment decision instruments. Although the Financial Accounting Standards Board (FASB) has recommended voluntary disclosure of unrecognised intangibles and the International Accounting Standards Board (IASB) has considered it essential that narrative reporting of intangibles should supplement financial statements, ways of addressing the issue are underdeveloped in Portugal. This paper seeks to redress that state by analysing the issue in the context of Portuguese Accounting Standards. We explore whether the Portuguese security market values intellectual capital and use our results to assess whether Portuguese financial statements are losing their relevance. We find that Portuguese accounting standards, based on accounting conservatism, give little attention to intangibles. Despite this, unrecognised intangibles seem to be increasing. Between 1995 and 1999, the market to book value ratio (MV/BV) of listed Portuguese companies increased, particularly in high technology and services companies. Whereas Intellectual Capital seems to be an important component of the market value of listed Portuguese companies, reporting practices are random and are based mainly on narrative.